Adaptation and Psychometric Investigation of the Family Role Performance Scale - Fauziah, Nailul; Sri Indrawati, Endang; Dinardinata, Adi (Universitas Ahmad Dahlan, 2024)
Family role performance refers to fulfilling responsibilities and expectations associated with various family roles. In urban Indonesia, changing gender roles and family dynamics have highlighted the importance of role division between spouses, but no studies have adapted a measurement tool into Indonesian. This study aims to adapt and test the psychometric validity of the Family Role Performance Scale by Chen et al. (2014) for Indonesian families, hypothesizing it will be a reliable tool. The research design is cross sectional, involving cultural adaptation and factor structure testing via Confirmatory Factor Analysis (CFA). Construct validity, convergent validity, and discriminant validity were also assessed. The sample consisted of 250 married couples, determined using a G-power of 0.8. Analysis results indicated that factor loading values above 0.5 demonstrate good validity and reliability, making the scale suitable for measuring role division in Indonesian families. These findings provide a reliable tool for assessing family role performance and supporting policies aimed at balancing family roles in a changing society.